Kinetic study and modelling of char combustion in TGA in isothermal conditions. (1st September 2017) - Morin, Mathieu; Pécate, Sébastien; Masi, Enrica; Hémati, Mehrdji
Highlights: Experimental study of biomass char combustion in TGA in isothermal conditions. Operating conditions: T < 400 °C, 5065 Pa < PO2 < 21, 273 Pa, dp = 25 μm. Response of the TGA to a concentration step included in the kinetic modelling. The GM and the RPM are the more appropriate models to represent kinetic data. Activation energy of 124 kJ/mol and reaction order with respect to oxygen of 0.74. Abstract: The purpose of this work is the kinetic study of biomass char combustion in isothermal conditions in TGA. This char was obtained from fast pyrolysis of beech bark pellet in a fluidized bed reactor at 850 °C and atmospheric pressure. Kinetic study of isothermal char combustion was performed for temperatures up to 400 °C, oxygen partial pressures ranging from 5065 to 21, 273 Pa and a char particles size of 25 μm. Mass transfer effects around and within the crucible were thoroughly characterized by naphthalene vaporization. Oxygen diffusion was found to have no effect on char combustion for temperatures below 400 °C. A novel method including the transfer function of the TGA which describes the variation of oxygen partial pressure just after switching the gas from inert to reactive in the TGA was taken into consideration in the kinetic modelling. Two kinetic models (the Grain Model and the Random Pore Model) were used to determine kinetic parameters. The Grain Model was found to be in very good agreement with experimental data. Values of activation energy and reaction order with respect to oxygen are respectively equal to 124 kJ/mol and 0.74. Besides, the maximum combustion rate commonly observed in the literature during char combustion was found to be the result of the non-uniform oxygen partial pressure in the TGA at the initial stage of the char combustion.